공개형 블록체인을 활용한 신뢰기반 감염병 관리 시스템 - 장경배(Kyung-Bae Jang); 박재훈(Jae-Hoon Park); 서화정(Hwa-Jeong Seo) (한국정보통신학회논문지, 2020)
In the event of a fatal infectious disease in the country, it is very important that the government respond quickly and prevent the secondary infection of the people to prevent the subsequent spread of damage. However, in order to detect infectious diseases in existing medical institutions, and to reach the KCDCP(Korea Centers for Disease Control and Prevention) a total of four steps must be taken. In this paper, we simplifies the existing reporting process using the open blockchain. In addition, not only infectious disease related organizations share infectious disease information on the blockchain, but also grant access to the blockchain to ordinary citizens. By sharing information quickly and transparently revealing the process, we can add credibility to the response to the outbreak and official announcements. The public can also build efficient next-generation defense systems by checking information on the blockchain to prevent secondary infections. 국가에 치명적인 감염병이 발생하였을 때, 점차 퍼지는 후속 피해를 막기 위해서는 정부의 신속한 대처와 국민들의 2차 감염 예방이 매우 중요하다. 하지만 기존 의료기관에서 감염병을 발견하고, 이 사실이 질병관리본부까지 도달하기에는 총 4단계의 보고절차를 밟아야 한다. 이에 본 논문에서는 공개형 블록체인을 활용하여 기존 보고절차를 간소화 한다. 또한 감염병 관련 기관들만이 블록체인에서 감염병 정보를 공유하는 것이 아니라, 블록체인의 열람권한을 일반 시민들에게도 부여한다. 빠르게 정보를 공유하고 처리과정을 투명하게 공개하여 감염병 발생에 대한 대처와 공식발표에 신뢰를 더할 수 있다. 국민들 또한 2차 감염을 예방하기 위한 정보들을 블록체인에서 확인하여 효율적인 차세대 방역체계를 구축할 수 있다.